Immunohistochemical Analysis of Non-Small Cell Lung Cancer: Correlation with Clinical Parameters and Prognosis - Yoo, Jinyoung; Jung, Ji Han; Lee, Myung A; Seo, Kyung Jin; Shim, Byoung Yong; Kim, Sung Hwan; Cho, Deog Gon; Ahn, Myeong Im; Kim, Chi Hong; Cho, Kyu Do; Kang, Seok Jin; Kim, Hoon Kyo (Journal of Korean medical science, 2007)
Non-small cell lung cancers (NSCLC) vary in their biologic behavior. Recurrence and tumor-related mortality may be attributable to molecular abnormalities in primary tumors. This study evaluated such immunophenotypes with regard to cell cycle regulation and proliferation, apoptosis, and angiogenesis, to determine their significance for patient outcome. Core biopsies from 219 patients with NSCLC were assembled on tissue microarrays, and the expressions of p16, p21, p27, cyclin B1, cyclin E, Ki-67, caspase-3, survivin, bcl-2, VEGF, and endostatin were evaluated by immunohistochemistry. Despite previously described prognostic relevance of some of the investigated molecules, many of those markers were not directly associated with recurrence or survival. However, there was a trend for p16 immunoreactivity to be associated with a good prognosis (57% vs. 42% in 5-yr survival) (p=0.071). bcl-2 expression was strongly correlated with a better outcome (65% vs. 45% in 5-yr survival) (p=0.029), and the hazard of death for bcl-2 positive patients was 0.42 times of that for bcl-2 negative patients (p=0.047). A multivariate analysis with Cox proportional hazards model confirmed that the lymph node status (p=0.043) and stage (p=0.003) were other independent prognostic factors. Our results suggest that p16 and bcl-2 provide prognostic information independent of the TNM stage in NSCLC.